2018
DOI: 10.1590/1807-3107bor-2018.vol32.0019
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological analysis and need for endodontic treatment among the indigenous Sateré-Mawé and Tikuna

Abstract: The objective of this study was to analyze the epidemiological profile of oral health of Sateré-Mawé indigenous people living in Barreirinha, Amazonas (AM), Brazil, and the Tikuna indigenous people living in the urban area of Manaus (AM), in addition to characterizing the need for endodontic treatment between the two ethnic groups. A total of 138 individuals participated in the study, of whom 98 were Tikuna and 40 were Sateré-Mawé; they were distributed in age groups ranging from seven to 75 years. A very high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…The severity of dental caries observed in this study, expressed by the DMFT index, is close to the mean scores reported to the Indigenous peoples Guarani (13.9) and Xavante (14.25) in the 35-44 age bracket 17,18 . A study conducted with Sateré-Mawé and Tikuna Indigenous peoples from Brazil observed mean DMFT of 13.4 for adults aged 40 to 49 years old 11 . Higher DMFT scores were previously described among the Potiguara (16.43), Indigenous adults from the Xingu National Park (20.2), and non-Indigenous adults in Brazil (16.75) 12,19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of dental caries observed in this study, expressed by the DMFT index, is close to the mean scores reported to the Indigenous peoples Guarani (13.9) and Xavante (14.25) in the 35-44 age bracket 17,18 . A study conducted with Sateré-Mawé and Tikuna Indigenous peoples from Brazil observed mean DMFT of 13.4 for adults aged 40 to 49 years old 11 . Higher DMFT scores were previously described among the Potiguara (16.43), Indigenous adults from the Xingu National Park (20.2), and non-Indigenous adults in Brazil (16.75) 12,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Data from the 2010 National Oral Health Survey shows that Brazilian urban Indigenous adults present a mean Decayed, Missing and Filled teeth (DMFT) index of 17.1, similar to the non-indigenous urban population (16.9) 10 . Nevertheless, recent studies conducted with Indigenous adults living in traditional territories demonstrate a rather heterogeneous situation, with DMFT ranging from 13.4 to 20.2 11,12 . Additionally, vulnerable groups tend to be significantly affected by tooth loss, a strong manifestation of oral health inequalities 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, indigenous and black children showed significant more untreated dental caries than white children, which is in accordance with the less favourable reality faced by the black and indigenous communities living in urban areas that face cultural barriers to access dental treatment and still presents low educational level. 29 Due to the cross-sectional nature of the study, a causal relationship between the variables cannot be established and the interpretation of the observed associations must rely on assumptions informed by the theoretical model. Although a significant association between underweight nutritional status and dental caries was shown, it was not possible to clarify the direction of this association.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in this population caregiver's schooling was linearly associated with children's good oral health. On the other hand, indigenous and black children showed significant more untreated dental caries than white children, which is in accordance with the less favourable reality faced by the black and indigenous communities living in urban areas that face cultural barriers to access dental treatment and still presents low educational level …”
Section: Discussionmentioning
confidence: 99%
“…In short, the data on the prevalence of RFT differs from one study to another, reflecting the differences in the needs and availability of RCT in different countries and populations (Caires et al, 2018 ; Connert et al, 2019 ), as well as the different impact of the new diagnostic and therapeutic trends in the management of deep carious lesions and pulpitis (Crespo‐Gallardo et al, 2019 ; Edwards et al, 2021 ; Wolters et al, 2017 ). Knowing the prevalence of RFT in the worldwide will allow dentists and policy makers to evaluate the impact that RCT has on the world population.…”
Section: Introductionmentioning
confidence: 99%